Successful tracheal intubation with video laryngoscope when awake fiberoptic bronchoscopy failed in a patient with hypopharyngeal mass - Goyal, Somnath; Kulkarni, Anita (Journal of Society of Anesthesiologists of Nepal, 2017)
Video laryngoscope is one of best alternative in managing difficult airways. Our patient presented with left side neck pain and hoarseness of voice for three months, dysphagia to solids for two months. Computed tomography revealed large hypopharyngeal mass and a diagnosis of carcinoma of hypopharynx was made. As endoscopic Ryle’s tube insertion by gastroenterologist was unsuccessful so he was posted for Feeding jejunostomy under general anaesthesia. We anticipated difficult endotracheal intubation. Our first attempt to secure airway with awake fiberoptic bronchoscopic intubation was unsuccessful. Using an alternative method with bougie and video laryngoscopy, the trachea was successfully intubated. In rare clinical scenario fiberoptic bronchoscopic intubation may fail, hence we need to be prepared with the backup plan for airway management. A video laryngoscope might be useful in such situations.